mSphere of Influence: The maternal gut–mammary axis and its role in shaping neonatal health - Stephanie N. Langel (mSphere)
ABSTRACT Stephanie Langel works in the field of breast milk immunity and maternal-neonatal health. In this mSphere of Influence article, she reflects on how three pivotal papers—Roux et al. (J Exp Med 146:1311–1322, 1977, https://doi.org/10.1084/jem.146.5.1311), Wilson and Butcher (J Exp Med 200:805–809, 2004, https://doi.org/10.1084/jem.20041069), and Rogier et al. (Proc Natl Acad Sci USA 111:3074–3079, 2014, https://doi.org/10.1073/pnas.1315792111)—made an impact on her by uncovering the critical pathways and mechanisms through which gut-derived IgA-secreting cells migrate to the mammary gland and secrete antibodies against intestinal microbes. These foundational studies shaped her understanding of the gut–mammary axis and continue to inspire her research aimed at advancing maternal and neonatal health through breast milk immunology.